RELATIONSHIP BETWEEN WORK AND ANXIETY OF PRIMIGRAVIDA PREGNANT WOMEN IN TRIMESTER III IN FACING CHILDBIRTH AT BATU AJI COMMUNITY HEALTH CENTER - Fitta Deskawaty; Roni Aldiano (Universitas Batam, 2020)
Background : Suyati et al (2011) conducted a study on the relationship between knowledge of pregnant women about the delivery process and the level of anxiety in facing childbirth. It was found that out of 48 pregnant women, 13 pregnant women (27.1%) had sufficient knowledge and experienced severe anxiety. This is because the understanding of a pregnant woman to know the process of childbirth is very important because pregnant women often have disturbing thoughts, as a development of an anxiety reaction to the stories they get. A number of fears arise in the third trimester. Pregnant women will feel anxious about the life of the baby and his own life, such as: whether the baby will be born normally. The purpose of this study is the relationship between work and the anxiety of primigravida pregnant women trimester III in dealing with childbirth. Method : The design in this study was cross sectional. The research was carried out at Puskesmas Batu Aji. The population in this study were all trimester III primigravida pregnant women who visited and performed ANC examinations. The sampling technique used in this study was total sampling. The instrument in this study used a questionnaire sheet and a check list. To measure the level of anxiety using the Hamilton Rating Scale for Anxiety (HRS-A). Chi-Square hypothesis test. Result : Research Results From the results of the chi-square calculation, the p-value is 0.571, which means that the p-value is â‰¥ 0.05. Conclusion : The conclusion is that there is a relationship between work and the anxiety of primigravida pregnant women trimester III in dealing with childbirth